A Combined Effect of Self and Reward: Relationship of Self- and Reward-Bias on Associative Learning - Wang, Lingyun; Qi, Yuxin; Li, Lihong; Jia, Fanli (Frontiers in Psychology, 2021)
Past research has demonstrated that individuals process information related to oneself or a high reward quickly and has referred to this as self-bias or reward-bias. However, no past study has presented self- and reward-bias simultaneously. The present study investigated perceptual processing using the associated learning paradigm when both self and reward were prioritized (double salience condition) as well as when either self or reward was prioritized (single salience condition). The present study established these two conditions by manipulating self-relevance (self vs. stranger in experiment 1; self vs. friend in experiment 2). The results showed that (1) When the self was pitted against a stranger and received a high or low reward, participants’ perceptual processing mainly involved self-bias (experiment 1); (2) When the self was pitted against a friend, perceptual processing involved both self-bias and reward-bias (experiment 2). The study revealed a complex relationship between self- and reward-bias, which depends on the degree of affinity between oneself and others.